Benny's New Friend - Warner, Gertrude Chandler; Nang Chan Yeema (Morton Grove, IL, United States Albert Whitman & Company, 1998)
Benny anticipates making friends with new kid down the street, but when he finds out that she's a girl, he is very disappointed.
Keywords: Story Collection